Measuring Violent Conflict in Micro-Level Surveys : Current Practices and Methodological Challenges - Bruck, Tilman; Justino, Patricia; Verwimp, Philip; Tedesco, Andrew (World Bank, Washington, DC, 2016)
This paper reviews both current practices and common challenges of measuring the causes, functioning, and consequences of violent conflict at the micro-level. The authors review existing conflict -- and violence-related survey questionnaires, with a particular focus on the World Bank's Living Standard Measurement Surveys. Further, they discuss methodological challenges associated with empirical work in conflict-affected areas—such as operationalizing a definition of conflict, using the appropriate units of analysis, deciding on the timing of the survey, dealing with data biases and conducting surveys in an ethically sound manner—and propose ways to improve the usefulness of existing surveys to analyze conflict processes at the micro-level. Violent conflict, households, survey methods, questionnaire design.